Creating mindful heroes: a case study with ninth grade students - Nogueira, Inês; Barbosa, Mariana Reis; Ribeiro, Luísa Mota; Xenophontos, Ioanna; Zimbardo, Philip (Frontiers in Psychology, 2023)
The Heroic Imagination Project (HIP) seeks to redefine heroism as a set of habits possible for anyone to achieve. Research findings on the psychological foundations of negative forms of social influence that can lead to bystander behavior are translated into tools that individuals can use in their everyday lives. Habits of wise and effective helping behavior are learned, modeled and encouraged through the training of the ‘heroic imagination’. According to literature, practicing mindfulness can lead to an increase of empathy, compassion and pro-social behaviours. There is empirical evidence that compassion can be a mediator between mindfulness and pro-social helping behaviours towards strangers, suggesting that mindfulness promotes this behaviour, contributing to overcome the bystander effect. With this hypothesis in mind, we created a programme that incorporated both Mindfulness and HIP sessions. Five participants volunteered to participate in the “Creating Mindful Heroes” nine-week programme. Throughout the sessions they filled in a diary, and at the end of the programme, they answered two feedback questionnaires. They were then invited to participate in individual interviews. The participants reported a positive overall perspective regarding the programme, mentioning several improvements in their relationships regarding their family, peers and with others in society. Moreover, it was described by the participants that the programme promoted prosocial behaviours and aided them regarding their empathy.